Self-Esteem and Strategies for Coping with a Social Conflict Situation Preferred by Adolescents - Borecka-Biernat, Danuta (Przegląd Badań Edukacyjnych (Educational Studies Review), 2020)
The purpose of the study was to find out relationships between the level of self-esteem and the occurrence of destructive (aggression, avoidance, submission) and constructive (taskoriented) strategies for coping with a social conflict situation by adolescents. The study used M. Rosenberg’s Self-Esteem Scale (SES) adapted by M. Łaguna, K. Lachowicz-Tabaczek and I. Dwonkowska as well as the Questionnaire to study strategies for coping with a social conflict situation by adolescents (KSMK) by D. Borecka-Biernat. The empirical research was carried out in junior high schools in Wroclaw (and neighbouring towns). They included 893 adolescents (468 girls and 425 boys) aged 13–15. The analysis of research results indicates that a lower assessment of a young person’s own abilities coexists with a tendency to react destructively to a conflict. The study also showed that adolescents with a higher self-esteem who find themselves in a conflict situation will take advantage of a constructive strategy to deal with this situation. The research results regarding the personality premise of the strategy for coping with a social conflict situation by youth have practical significance. It is particularly worth paying attention to it in the course of upbringing and education of adolescents in order to shape their ability of effective and ethical coping with conflict situations.